The Guernsey Literary and Potato Peel Pie Society - Shaffer, Mary Ann; Barrows, Annie (New York, N.Y. : Dial Press Trade Paperbacks, 2009)
As London is emerging from the shadow of World War II, writer Juliet Ashton discovers her next subject in a book club on Guernsey--a club born as a spur-of-the-moment alibi after its members are discovered breaking curfew by the Germans occupying their island.
Originally published: New York : The Dial Press, 2008.
Includes a reader's guide.
Keywords: Women authors -- Fiction; Book clubs (Discussion groups) -- Fiction; London (England) -- Fiction -- History -- 20th century; Channel Islands -- Fiction -- History -- German occupation, 1940-1945; Guernsey (Channel Islands) -- Fiction; England -- Fiction